Bio-fortification of iron and zinc improves the biomass, uptake, distribution and yield of different maize varieties - Qureshi, Muhammad Tamoor; Iqbal, Nasir; Noorka, Ijaz Rasool; Waheed, Hasnain (Journal of plant nutrition, 2020)
Different approaches are underway to enrich the crops with nutrients to fulfill the nutrition requirement. This study was performed to investigate the impact of Zn and Fe bio-fortification on different maize varieties. Four maize varieties: V 1 (Pak 2); V 2 (Golden); V 3 (Sultan); V 4 (Pearl) and three treatments: T 1 (control-untreated), T 2 (Iron 7 mg/L as FeSO 4 .7H 2 O) and T 3 (Zinc 10 mg/L as ZnSO 4 .5H 2 O) were used. The variety V 2 performed better and produced highest biomass, leaf area, seed yield, total iron (TIC) and zinc concentration (TZC). In case of trace elements, maximum biomass, leaf area and seed yield was observed under T 3 . Moreover, highest TIC (62.90 mg kg −1 ) and TZC (65.80 mg kg −1 ) was measured with T 2 and T 3 , respectively. The highest iron and zinc in stover (33.14 & 33.79 mg kg −1 ) and grain (29.75 & 32.00 mg kg −1 ) were determined with T 2 and T 3 , respectively. In these experiments, V 2 produced highest net income (NI) (615.02 US $ha −1 ) and among trace elements, T 3 gave maximum NI (629.83 US $ha −1 ). Overall, maize varieties with T 3 had 24% higher NI than T 1 . As growth, yield and NI were improved with V 2 under T 3 , therefore this combination was most effective for maize production.